HARMONIZING ISLAMIC VALUES WITH TECHNOLOGICAL ADVANCEMENTS FOR SELF-DEVELOPMENT - Ramadhan, Yusfar; Asykur, Asykur; Ali, Ahmad Zulfikar; Mujibno, Mujibno (Universitas Al-Amien Prenduan, 2023)
The development of learning innovation in the era of